The underground library eaudiobook A novel. - Ryan, Jennifer (Books on Tape, 2024)
When the Blitz imperils the heart of a London neighborhood, three young women must use their fighting spirit to save the community’s beloved library in this novel based on true events from the author of The Chilbury Ladies ’ Choir. When the new deputy librarian, Juliet Lansdown, finds that Bethnal Green Library isn’t the bustling hub she is expecting, she becomes determined to breathe life back into it. But can she show the men in charge that a woman is up to the task of running the library, especially when a confrontation with her past threatens to derail her? Katie Upwood is thrilled to be working at the library, although she is only there until she heads off to university in the fall. But after the death of her beau on the front line and amid tumultuous family strife, she finds herself harboring a life-changing secret with no one to turn to for help. Sofie Baumann, a young Jewish refugee, came to London on a domestic service visa only to find herself working as a maid for a man who treats her abominably. She escapes to the library every chance she can, finding friendship in the literary community and aid in finding her sister, who is still trying to flee occupied Europe. When a slew of bombs destroys the library, Juliet relocates the stacks to the local Underground station where the city’s residents shelter nightly, determined to lend out stories that will keep spirits up. But tragedy after tragedy threatens to unmoor the women and sever the ties of their community. Will Juliet, Kate, and Sofie be able to overcome their own troubles to save the library? Or will the beating heart of their neighborhood be lost forever?